IDENTITY DISCOURSE IN LOCAL NEWSPAPERS BEFORE, DURING, AND AFTER MILITARY CONFLICT: A CASE STUDY OF KRAMATORSK. - ROOZENBEEK, JON (Demokratizatsiya)
This article investigates identity discourse during military conflict through the lens of local print media. Using dynamic topic modelling and the term frequency-inverse document frequency statistic, this article examines what discursive themes appeared in two local newspapers from the city of Kramatorsk in eastern Ukraine before, during and after a threemonth occupation by militants of the so-called Donetsk "People's Republic" (DNR) in 2014; how these themes evolved over time; and how these themes related to local, regional, and national identity discourse. The results show that the conflict fueled the replacement of local and regional identity discourses with a national (Ukrainian) discourse, even as the conflict receded from view as a topic of discussion. Moreover, there is no indication that representatives of the DNR engaged in efforts to either foster a new identity or hark back to historical, political, or cultural references for identitybuilding purposes.